Long-term effects of restriction of intravenous fluid in adult ICU patients with septic shock - Kjær, Maj-Brit Nørregaard; Meyhoff, Tine Sylvest; Sivapalan, Praleene; Granholm, Anders; Hjortrup, Peter Buhl; Madsen, Martin Bruun; Møller, Morten Hylander; Egerod, Ingrid; Wetterslev, Jørn; Lange, Theis; Cronhjort, Maria; Laake, Jon Henrik; et al. (Intensive care medicine, 2023)
PURPOSE: To assess long-term outcomes of restrictive versus standard intravenous (IV) fluid therapy in adult intensive care unit (ICU) patients with septic shock included in the European Conservative versus Liberal Approach to Fluid Therapy in Septic Shock in Intensive Care (CLASSIC) trial. METHODS: We conducted the pre-planned analyses of mortality, health-related quality of life (HRQoL) using EuroQol (EQ)-5D-5L index values and EQ visual analogue scale (VAS), and cognitive function using Mini Montreal Cognitive Assessment (Mini MoCA) test at 1 year. Deceased patients were assigned numerical zero for HRQoL as a state equal to death and zero for cognitive function outcomes as worst possible score, and we used multiple imputation for missing data on HRQoL and cognitive function. RESULTS: Among 1554 randomized patients, we obtained 1-year data on mortality in 97.9% of patients, HRQoL in 91.3%, and cognitive function in 86.3%. One-year mortality was 385/746 (51.3%) in the restrictive-fluid group versus 383/767 (49.9%) in the standard-fluid group, absolute risk difference 1.5%-points [99% confidence interval (CI) - 4.8 to 7.8]. Mean differences were 0.00 (99% CI - 0.06 to 0.05) for EQ-5D-5L index values, - 0.65 for EQ VAS (- 5.40 to 4.08), and - 0.14 for Mini MoCA (- 1.59 to 1.14) for the restrictive-fluid group versus the standard-fluid group. The results for survivors only were similar in both groups. CONCLUSIONS: Among adult ICU patients with septic shock, restrictive versus standard IV fluid therapy resulted in similar survival, HRQoL, and cognitive function at 1 year, but clinically important differences could not be ruled out.
Keywords: dospělí; jednotky intenzivní péče; Intravenous fluid; Adult; Sepsis; kvalita života; lidé; péče o pacienty v kritickém stavu; přežívající; Shock, Septic; Long-term outcomes; Intensive Care Units; Critical Care; septický šok; Critical illness; Quality of life; Septic shock; Cognitive function; Survivors; Quality of Life; Humans